A Study on the Nasal Index of Malocclusion Patients Using Cone-Beam Computed Tomography 3D Program - Sung-Suk Bae; Hee-Jeung Jee; Yun-Ja Hwang; Ha-Rin Jang; Su-Jeong Kang; Jeong-Hyun Lee (The Korean Society of Dental Hygiene Science, 2024)
Background: Research is continuously being conducted on the relationship between the airway and malocclusion. The nose, as the upper part of the respiratory pathway, plays a critical role. While various international studies employ the Nasal Index classification for nasal morphology, domestic research remains scarce. This research investigates the proportions of nasal morphology in malocclusion patients utilizing a 3D software. Methods: The study evaluated 100 malocclusion patients in their 20s (40 Class I, 34 Class II, 26 Class III). Cone-beam computed tomography was used with the Mimics (ver. 22; Materialise) 3D program to model the skull and soft tissues of the patients in three views: coronal, sagittal, and frontal. Results: The results showed that in Class I, there were 5 leptorrhine (long and narrow) cases, 30 mesorrhine (moderate shape) cases, and 5 platyrrhine (broad and short) cases. In Class II, there were 3 leptorrhine, 25 mesorrhine, and 6 platyrrhine cases. In Class III, there were 2 leptorrhine, 21 mesorrhine, and 3 platyrrhine cases. Conclusion: The findings of this study indicate that there is no significant correlation between the size of the nose and malocclusion in patients. Additionally, additional research related to this study is expected to be necessary.